Smart win–win waste management: superhydrophobic filter using valorized cellulose acetate from discarded cigarette butts for cleaning up marine oil spill at Hurghada Red Sea shore in Egypt - Nabwey, Hossam A.; Abdelkreem, Maha; Tony, Maha A.; Al Hoseny, Noha F. (Frontiers in Marine Science, 2024)
The essential target of academics and the industrial sector is the innovation of an industrial ecology approach. Worldwide, cigarette butts (CBs) comprise the most predominant form of litter that spreads into the ecosystem and inland. In the meantime, oil is spilled into marine life from various activities and transportation. The result is a complex oil–water composition in a high concentration that causes severe hazards to the environment and to aquatic life. In this regard, the current investigation focuses on obtaining hydrophobic cellulose acetate from CBs for use as a filter media. The filter is applied in marine oil spill separation as a win–win industrial ecology technique. Initially, the separated CB residuals were prepared by successive washing. Subsequently, the obtained cellulose acetate fibers were characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Furthermore, the new CB-based filters were used in the separation/adsorption of marine oil wastewater spill. Subsequently, a group of experiments were conducted. The results showed that the cleanup efficiency could be up to 99% in terms of chemical oxygen demand (COD). Moreover, the products were recovered by washing with hot water for further use, which showed high removal activity that reached 95% after successive uses. In comparison to commercial oil sorption materials, the results were promising as the RP-C18 cartridge revealed a maximum oil removal of 90%. Such preliminary data on a cellulose acetate filter scheme are a good indicator in the development of an oil spill facility, being a suitable candidate for controlling oil wastewater effluent streams.